2005
DOI: 10.1007/s00445-005-0431-9
|View full text |Cite
|
Sign up to set email alerts
|

Petrological characteristics and volatile content of magma from the 2000 eruption of Miyakejima Volcano, Japan

Abstract: Bull Volcanol (2005) 67(3): 268-280In the original online publication and the print version of this article, Tables 1 and 2 were unfortunately omitted. We apologise for this error. The tables are printed below.The online version of the original article can be found at http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
62
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(70 citation statements)
references
References 0 publications
8
62
0
Order By: Relevance
“…Indeed, reported H 2 O content of plagioclase-hosted basal-438 M. Hamada and T. Fujii accumulation of plagioclase in the upper parts of magma chambers beneath the Izu-Oshima volcano, which required less than 0.7 wt.% H 2 O to float plagioclase in melt. Analyses of H 2 O in plagioclase-hosted melt inclusions (e.g., 1.0 wt.% on average at Izu-Oshima volcano by Kazahaya et al, 1994; 0.9 to 1.9 wt.% at Miyakejima volcano in Izu arc by Saito et al, 2005) seem to be consistent with previous suggestions of a small amount of H 2 O (~1 wt.%) in island arc basalt at the volcanic front.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, reported H 2 O content of plagioclase-hosted basal-438 M. Hamada and T. Fujii accumulation of plagioclase in the upper parts of magma chambers beneath the Izu-Oshima volcano, which required less than 0.7 wt.% H 2 O to float plagioclase in melt. Analyses of H 2 O in plagioclase-hosted melt inclusions (e.g., 1.0 wt.% on average at Izu-Oshima volcano by Kazahaya et al, 1994; 0.9 to 1.9 wt.% at Miyakejima volcano in Izu arc by Saito et al, 2005) seem to be consistent with previous suggestions of a small amount of H 2 O (~1 wt.%) in island arc basalt at the volcanic front.…”
Section: Introductionsupporting
confidence: 88%
“…Indeed, reported H 2 O content of plagioclase-hosted basal-438 M. Hamada and T. Fujii accumulation of plagioclase in the upper parts of magma chambers beneath the Izu-Oshima volcano, which required less than 0.7 wt.% H 2 O to float plagioclase in melt. Analyses of H 2 O in plagioclase-hosted melt inclusions (e.g., 1.0 wt.% on average at Izu-Oshima volcano by Kazahaya et al, 1994; 0.9 to 1.9 wt.% at Miyakejima volcano in Izu arc by Saito et al, 2005) seem to be consistent with previous suggestions of a small amount of H 2 O (~1 wt.%) in island arc basalt at the volcanic front.The question remains as to whether Ca-rich plagioclase in island arc basalt crystallized from melts with smaller amounts of H 2 O (~1 wt.%) than the values expected from Ca/Na partition equilibrium from experimental studies (up to 6 wt.%). It is possible to assume that Ca-rich plagioclase is not in equilibrium with matrix (melt) composition.…”
supporting
confidence: 88%
“…This tholeiitic differentiation trend has been reproduced in melting experiments with anhydrous basalts at 0.1 MPa and on low-H 2 O (≤2 wt.%) basalts at low pressure (≤200 MPa; e.g., Grove and Baker 1984;Hamada and Fujii 2008;Tatsumi and Suzuki 2009;Zimmer et al 2010), which is consistent with the low H 2 O (≤2 wt.%) recorded in melt inclusions (e.g., Kazahaya et al 1994;Saito et al 2005).…”
Section: Introductionsupporting
confidence: 77%
“…On the contrary, recent melt inclusion studies (e.g. Sisson and Layne 1993;Newman et al 2000;Saito et al 2005Saito et al , 2010Ikehata et al 2010) indicated that the H 2 O content in tholeiitic basaltic melt is larger than 3 wt.% at the volcanic front.…”
Section: Introductionmentioning
confidence: 93%
“…In the case of Izu-Oshima volcano, the maximum H 2 O content of melt inclusions in the olivine phenocrysts was 3.4 wt.% by analysis of products of the older Oshima group (Ikehata et al 2010). In the case of Miyakejima volcano, Saito et al (2005Saito et al ( , 2010 analyzed melt inclusions of plagioclase and olivine phenocrysts from the AD 2000 eruption and estimated the H 2 O content to be 3.3 wt.% in olivine-hosted melt inclusions. These analyses are consistent with the values of pre-eruptive H 2 O content in melt estimated in this study.…”
Section: Pre-eruptive H 2 O Content In Arc Basalt Magmasmentioning
confidence: 99%